2021
DOI: 10.15275/rusomj.2021.0115
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related specificities of photoplethysmogram spectral assessment dynamics in healthy subjects during the passive tilt test

Abstract: The goal of our study was to investigate gender-related specificities of photoplethysmogram (PPG) spectral assessment dynamics in healthy individuals during the passive tilt test. Material and Methods — The study involved 38 men (33±7 years old) and 15 women (27±8 years old). The PPG signal was recorded for 10 minutes in the horizontal and vertical positions of the human body (passive tilt test). The following spectral parameters of PPG were calculated: HF%, LF%, and LF/HF. Results — In the horizontal body pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…PPG signals also provide opportunities to assess the parameters of blood pressure (BP) and peripheral blood flow. [ 52 – 54 ]. Almarshad et al showed that PPG and BP signals have the same frequency components as sequences of RR intervals in the LF band [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPG signals also provide opportunities to assess the parameters of blood pressure (BP) and peripheral blood flow. [ 52 – 54 ]. Almarshad et al showed that PPG and BP signals have the same frequency components as sequences of RR intervals in the LF band [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the high coherence between BP and PPG signals, it is possible to study autonomic control of blood pressure using the PPG signal instead of BP. Moreover, other studies have demonstrated the functional autonomy of the LF oscillations of the heart rhythm and peripheral blood flow by PPG signal analysis [ 53 , 54 ]. Extracting accurate HRV parameters and their oscillation is also desired for other health applications such as blood pressure measurement.…”
Section: Discussionmentioning
confidence: 99%